PAENIBACILLUS POLYMIXA, AS A CORE DIAZOTROPHIC ENDOLICHENIC NON PHOTOSYNTHETIC BACTERIOBIOME REPRESENTATIVE OF CORTICOLOUS PHYSCIA BIZIANA THALLUS (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
The unique organization of lichen thallus provides still unexplored environment for microbial communities. The study aimed to isolate and identify endolichenic non photosynthetic diazotrophic bacteria from the thallus of corticolous lichen species Physcia biziana. Two strains of chemoorganoheterotrophic endospore-forming bacteria were isolated and identified based on 16S rRNA gene sequence analysis as Paenibacillus polymyxa (> 93.54% similarity). Characterization of cultivable strains suggest the involvement of associated bacteria in nitrogen cycling. This study highlights the significance of studying the endobacteriobiome of lichens, as it is an important aspect of their multicomponent natural biofilm.
Keywords: Physcia biziana; endolichenic bacteriobiome; Paenibacillus polymixa; 16S rRNA genes